Interconversions of P and F intermediates of cytochrome c oxidase from Paracoccus denitrificans - von der Hocht, Iris (National Academy of Sciences, 2011)
Cytochrome c oxidase (CcO) is the terminal enzyme of the respiratory chain. This redox-driven proton pump catalyzes the four-electron reduction of molecular oxygen to water, one of the most fundamental processes in biology. Elucidation of the intermediate structures in the catalytic cycle is crucial for understanding both the mechanism of oxygen reduction and its coupling to proton pumping. Using CcO from Paracoccus denitrificans, we demonstrate that the artificial F state, classically generated by reaction with an excess of hydrogen peroxide, can be converted into a new P state (in contradiction to the conventional direction of the catalytic cycle) by addition of ammonia at pH 9. We suggest that ammonia coordinates directly to Cu(B) in the binuclear active center in this P state and discuss the chemical structures of both oxoferryl intermediates F and P. Our results are compatible with a superoxide bound to Cu(B) in the F state.